Mesoderm patterning and morphogenesis in the polychaete Alitta virens (Spiralia, Annelida): Expression of mesodermal markers Twist, Mox, Evx and functional role for MAP kinase signaling. (May 2016) - Kozin, Vitaly V.; Filimonova, Daria A.; Kupriashova, Ekaterina E.; Kostyuchenko, Roman P.
Abstract: Mesoderm represents the evolutionary youngest germ layer and forms numerous novel tissues in bilaterian animals. Despite the established conservation of the gene regulatory networks that drive mesoderm differentiation (e.g. myogenesis), mechanisms of mesoderm specification are highly variable in distant model species. Thus, broader phylogenetic sampling is required to reveal common features of mesoderm formation across bilaterians. Here we focus on a representative of Spiralia, the marine annelid Alitta virens, whose mesoderm development is still poorly investigated on the molecular level. We characterize three novel early mesodermal markers for A. virens – Twist, Mox, and Evx – which are differentially expressed within the mesodermal lineages. The Twist mRNA is ubiquitously distributed in the fertilized egg and exhibits specific expression in endomesodermal- and ectomesodermal-founder cells at gastrulation. Twist is expressed around the blastopore and later in a segmental metameric pattern. We consider this expression to be ancestral, and in support of the enterocoelic hypothesis of mesoderm evolution. We also revealed an early pattern of the MAPK activation in A. virens that is different from the previously reported pattern in spiralians. Inhibition of the MAPK pathway by U0126 disrupts the metameric Twist and Mox expression, indicating an early requirement of the MAPK cascade for proper morphogenesis of endomesodermal tissues. Highlights: Twist is an early pan-mesodermal marker in A. virens . Twist, Mox, and Evx are differentially expressed within the mesodermal lineages. Activation of MAPK signaling can be observed in distinct blastomeres from the 8-cell stage onward. MAPK activity is required for the future endomesoderm morphogenesis at the cleavage phase. Mesoderm formation varies greatly in Spiralia despite a conserved cleavage pattern.